Spatial Transformation in Shanghai: the strategy, institutional arrangement and planning procedures - the case of EXPO 2010 - Ziye Na; Mingwei Liu (European Regional Science Association (ERSA), 2012)
As the economic center of China, Shanghai has achieved 8.2% of GDP increasing in 2011, and the GDP per capital reached 12 784, which is close to the level of some developed countries. Meanwhile, its urbanization rate has been 89% in 2009, the whole city is going through severe economic and spatial transformation and requalification. This paper aims to take EXPO 2010 as a case to interpret the strategic logic, institutional arrangement and planning procedures in Shanghai in recent years. The EXPO 2010 might be an extreme case not only because it is a public project in a very big scale, but also because it is the first time of a developing country holding EXPO, which gives this project political meaning - a successful EXPO is required for its international reputation. But it is exactly such a project that could reveal its real motivation, its institutional arrangement which the city considered as the most efficient, and the innovation of planning procedures which could be the paradigm of the future practice. The first part of the paper will introduce the identity card and the chronology of EXPO 2010, also the economic situation and spatial planning documents will be presented to help us understand the strategic purpose of EXPO 2010: it is a good opportunity for the city to transfer it economic structure from industrialization to post-industrialization, to revive the inner city, to integrate both sides of the important River crossing the city - Huangpu River, and to redefine Huangpu River as a symbol of post industrialization. In the succeeding parts, the leading strategy of pre-post strategy will be introduced: the planner stretched the planning effective date to 2020 when a world city is expected, and made the design backwards. In this way, the planning structure, the infrastructure and a big percentage of building which are constructed for EXPO 2010 will be directly put into operation after EXPO. In the institutional aspect, the urban government seems to play a role of developer: they turn the degraded industrial and residential land into prepared culture, business and top-class residential land, and release it to private developer again. In the planning procedure aspect, the chief planners, the decision makers and the implemental planner for the first time work closely, to make sure the plan could instruct the projects. Lastly, the theoretical base, breakthrough and criticisms will be discussed based on this case.
Keywords: 330